Imposition Of Criminal Sanctions for Minor Criminal Actions of Theft (A Case On Judgement Number 826/Pid.B/2023/Pn.Mtr) - Mandasari, Santi; Harun, Rina Rohayu; Jiwantara, Firzhal Arzhi; Septyanun, Nurjannah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The imposition of criminal sanctions for minor criminal actions, such as theft, presents a complex and multifaceted challenge for legal systems worldwide. This study examines the imposition of criminal sanctions for minor theft offenses, with a specific focus on the case adjudicated under Judgment Number 826/Pid.B/2023/Pn.Mtr. The research aims to analyze the legal reasoning behind the court's decision, the proportionality of the sanctions imposed, and the broader implications for the criminal justice system. Utilizing a qualitative approach, this study involves a detailed case analysis, reviewing court documents, and interviews with legal experts. Findings indicate that while the court adhered to statutory guidelines, there were significant considerations regarding the socio-economic background of the offender and the value of the stolen property. The study concludes that although the sanctions imposed were within legal parameters, there is a need for a more nuanced approach that considers restorative justice principles. This research contributes to the ongoing discourse on criminal justice reform, particularly concerning minor offenses, and advocates for policy adjustments that balance deterrence with rehabilitation.